Tradução e adaptação transcultural do questionário Foot and Ankle Ability Measure para o português do Brasil - Tarcisio Santos Moreira (2012)
The foot and ankle complex is the most affected area which is usually injured after trauma or due to overuse injuries that occur in many sport related activities or in routine activities of daily living. Frequently, these injuries lead to long-term functional limitations and in some cases they can lead to permanent impairments. The health impacts caused by injuries, illness or any other harm, especially on functionality and quality of life, should be considered in clinical assessment in health sciences. To quantify this functional impact represents a great challenge and also a goal for clinicians and researchers of health science, who employ client-based instruments to meet this need. Questionnaires and functional scales are tools which are able to include the domains of activity and participation and able to transform subjective measures into objective data. The Foot and Ankle Ability Measure questionnaire (FAAM) was identified as one of the best developed instruments to quantify functionality of individuals affected by musculoskeletal disorders of the ankle/foot complex, but its Portuguese version is still unavailable in Brazil. The FAAM is composed of two scales, one for the assessment of functionality during activities of daily living (ADL sub-scale) and another for sport-related actitivities (Sport sub-scale). The purpose of this study was to translate and cross-cultural adapt the FAAM and to verify the psychometric properties of the Brazilian-Portuguese version of this instrument. The analysis of the validity was carried out by applying the Rasch model, whereas test-retest reliability and internal consistency were analyzed with the Intraclass Correlation Coefficient (ICC1,1) and with Cronbach alpha, respectively. The psychometric properties of the FAAM-Brazil were verified in 55 volunteers from both genders, with a mean age of 34 years, with foot/ankle complex musculoskeletal disorders. The FAAM-Brazil showed ICC2,1 of 0,88 e 0,82 and Cronbach Alpha of 0,93 e 0,90 for the ADL and Sport sub-scales, respectively. The Rasch analysis indicated reliability coefficients of 0,92 and 0,88 for the individuals in the ADL and Sport subscale, respectively, and for the items, the values were 0,95 and 0,94 for both sub-scale on this same order. From the 29 items of the instrument, two from the ADL sub-scale (9,5%) and two from the Sport sub-scale (25%) did not match the expectations of the model, which compromised of the construct validity of the instrument. The item separation index for the ADL sub-scale was 4,17 and for the Sport sub-scale 3,89. For the ADL sub-scale, the individual separation index was 3,4 and 2,71 for the Sport sub-scale. The mean time of administration was seven minutes. The Brazilian version of the FAAM demonstrated to be valid and reliable when applied to Brazilian population, but the Rasch analysis results indicated that some items did not fit the model for the studied sample, because they showed an erratic pattern of response. Therefore, the FAAM-Brazil should be applied with caution to individuals who practice sports which physical demands are different from those described by the Sports sub-scale items.